(untitled) (The Pakistan Development Review, 1998)
In a memorable speech to the United Nations General Assembly, Nikita Krushehev predicted that communism would bury capitalism. In less emotive and more economistic terms, he was saying in effect that centrally planned economies would outperform market economies in terms of both output growth and social justice. History has not been kind to Krushehev. Not only central planning but even milder forms of state interventionism now stand discredited, and developing countries round the world are desperately trying to install functioning market economics. This sea-change in development philosophy generally owes something to donor conditionalities associated with structural adjustment credits, to the extent that “reforms” and “structural adjustment” have become virtually synonymous. Shortterm internal or external balance crises, and longer-term stagnation, also signalled to policy-makers the bankruptcy of over-interventionist policies—a lesson driven home by the phenomenal growth performance of the NIC’s, apparently the fruit of marketfriendly policies.